2014
DOI: 10.1136/annrheumdis-2014-eular.5162
|View full text |Cite
|
Sign up to set email alerts
|

FRI0400 Prognostic Role of Allelic Variations of Genes Affecting Haemostasis in the Development of Antiphospholipid Syndrome and Renal Damage in Patients with Systemic Lupus Erythematosus

Abstract: Background Secondary Antiphospholipid Syndrome (APS) can develop in 20-30% of patients with Systemic Lupus Erythematosus (SLE). Renal damage in the form of Lupus nephritis (LN) develops in 50-70% of SLE patients. Thrombotic microangiopathy (TMA) in patients with APS adds to the renal damage. It is known that risk of thrombotic complications increases when defects in genes affecting haemostasis are present. Objectives To study prognostic role of the PAI-1 (4G/5G 675), Factor XIII (G485T), FBG G (-455)A), GPIa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Moreover, 6 articles were manually added from previous meta-analyses. Excluded were: 61 repeated articles, 37 non-case–control studies, 56 articles without CKD, 11 articles focused on kidney transplantation patients, 8 articles for hereditary kidney disease, [ 45 – 60 ] 5 articles that did not provide complete genotype information, [ 22 , 61 64 ] 10 articles without MTHFR C677T, [ 65 74 ] 1 familial study, [ 75 ] 2 articles on minors, [ 76 , 77 ] 3 articles for auto-immune diseases, [ 78 80 ] 3 articles covering non-Asian and non-Caucasians, [ 81 – 83 ] 1 article with an incorrect definition of a control group, [ 84 ] 1 article using a duplicated population, [ 18 ] and 6 non-English articles. [ 85 – 90 ] Finally, 33 papers were included for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 6 articles were manually added from previous meta-analyses. Excluded were: 61 repeated articles, 37 non-case–control studies, 56 articles without CKD, 11 articles focused on kidney transplantation patients, 8 articles for hereditary kidney disease, [ 45 – 60 ] 5 articles that did not provide complete genotype information, [ 22 , 61 64 ] 10 articles without MTHFR C677T, [ 65 74 ] 1 familial study, [ 75 ] 2 articles on minors, [ 76 , 77 ] 3 articles for auto-immune diseases, [ 78 80 ] 3 articles covering non-Asian and non-Caucasians, [ 81 – 83 ] 1 article with an incorrect definition of a control group, [ 84 ] 1 article using a duplicated population, [ 18 ] and 6 non-English articles. [ 85 – 90 ] Finally, 33 papers were included for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…30 In contrast, previous studies did not identify any association between the PAI-1 4G/5G polymorphism and lupus susceptibility or its clinical expression in Russian, Bulgarian, Spanish, and Argentinean SLE cohorts with adult-onset disease. [31][32][33][34] Similarly, a recent meta-analysis of nine studies demonstrated that the PAI-1 4G/5G polymorphism did not increase the risk of SLE or LN among Asian and European populations, although they reported significant up-regulation of circulating PAI-1 activity in multi-ethnic cohorts with adult-onset SLE. 11 Ethnic background or gene-environmental interplay as well as differences in cohort size and studied age group may partly explain these discrepancies between our study and previously published data.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from NCF1 , several single nucleotide polymorphisms (SNPs) in NCF2 , NCF4 , and CYBA genes were reported to be associated with autoimmune diseases [ 15 17 ]. The results by Olsson et al indicated that the NCF4 rs729749 variant was involved in the development of RA in a Swedish cohort [ 16 ].…”
Section: Introductionmentioning
confidence: 99%